Atomic Layer Deposition of Electrocatalytic Insulator Al2O3 on Three-Dimensional Printed Nanocarbons - Ng, Siowwoon; Iffelsberger, Christian; Michalička, Jan; Pumera, Martin (ACS nano, 2021)
The advantages of three-dimensional (3D) printing technologies, such as rapid-prototyping and the freedom to customize electrodes in any design, have elevated the benchmark of conventional electrochemical studies. Furthermore, the 3D printed electrodes conveniently accommodate other active layers for diverse applications such as energy storage, catalysis, and sensors. Nevertheless, to enhance a complex 3D structure while preserving the fine morphology, conformal deposition by atomic layer deposition (ALD) technique is a powerful solution. Herein, we present the concept of coating Al2O3 by ALD with different thicknesses from 20 to 120 cycles on the 3D printed nanocarbon/PLA electrodes for the electrocatalytic oxidation of catechol as an important biomarker. Overall, 80 ALD cycle Al2O3 achieved an optimum thickness for catechol electrocatalysis. This is resonated with the enhanced adsorption of catechol at the electrode surface and efficient electron transfer, according to the two-proton, two-electron-transfer mechanism, as well as for the passivation of surface defects of the nanocarbon electrode. This work compellingly demonstrates the prospect of 3D printed electrodes modified by a functional layer utilizing a low-temperature ALD process that can be extended to other arbitrary surfaces.
Keywords: nucleation; three-dimensional printing; scanning electrochemical microscope; catechol oxidation; Al2O3 coating; electrocatalyst; charge transfer